Research on hydrodynamic performance of S-type turbine based on linear wave. - LingJie Bao; Ying Wang; JunHua Chen; Hao Li; ChuHua Jiang; Yue Zhuo; Siru Wu (PLoS ONE)
The hydrodynamic performance of a Savonius type turbine (S-type turbine) in wave field is studied. The method of combining numerical simulation with physical experiment is adopted.Based on linear wave theory and turbulence model, Star CCM+numerical simulation software is used for digital modeling, and overlapping grid technology is used for grid modeling. Dynamic Fluid Body Interaction (DFBI) model is called to control the movement of S-type turbine, and second-order time discretization is adopted to establish a two-dimensional wave field model and conduct numerical simulation. At the same time, the physical test system of S-type turbine was developed for physical experiment verification, and the rotating performance of S-type turbine under different wave heights and pe-riods was measured, and the results of numerical simulation and physical experiment were com-prehensively evaluated. The results show that in wave field, the inverted S-shape arrangement of horizontal axis is better than the positive S-shape arrangement of horizontal axis and the vertical axis arrangement, and the captured energy is more than 3 times. At the same time, the fluctuating rotation speed of S-type turbine in wave field needs to be close to the wave frequency to capture more wave energy, which has guiding significance for practical engineering.